Vitamin D receptor polymorphism and prostate cancer prognosis. (16th December 2022) - El-attar, Ahmed Z.; Hussein, Samia; Salama, Mariam F. A.; Ibrahim, Hanaa M.; AlKaramany, Amira S.; Elsawi, Mansour K.; Hemeda, Mohamed; Algazeery, Ahmed
Abstract: Background: Prostatic epithelial cells synthesize the active form of vitamin D (1, 25-dihydroxyvitamin D3 ), which participates in regulating prostate growth. Calcitriol, a synthetic form of vitamin D3, exhibits antiproliferative and prodifferentiation activities in prostate cancer. The function of 1, 25-dihydroxyvitamin D3 is mediated by its binding to vitamin D receptor (VDR). VDR forms a heterodimer, typically with retinoid X receptor, to regulate vitamin D target genes. We evaluated the relationship between VDR polymorphism and clinical characteristics associated with prostate cancer risk and prognosis among Egyptian men. Materials and methods: This case-control study included 2 groups of patients: group A, a control group of 50 subjects with benign prostate hyperplasia, and group B, 50 subjects newly diagnosed with prostate cancer. All participants performed complete blood count, liver and kidney function tests, prostate specific antigen measurement, histopathological analysis and immunohistochemistry for Dickkopf Homolog 3. Restriction fragment length polymorphism-polymerase chain reaction as performed to detect VDR polymorphism. Results: Patients with prostate cancer and controls showed a significantly different CA genotype frequency ( p = 0.007). Furthermore, prostate-specific antigen levels were significantly different in different genotypes in patients with prostate cancer ( p < 0.001). Finally, T stage and the VDR ApaI C/A polymorphism were significantly associated ( p < 0.041). Conclusion: The VDR ApaI C/A polymorphism may be a diagnostic and prognostic marker for prostate cancer in Egyptian men.